The effects of children’s self-educational aspiration and self-efficacy on mathematics achievement: A moderated chained mediation model - Liu, Tour; Chen, Xueming; Liu, Mengjun; Zhang, Yingbin; Xin, Tao; Wang, Yehui (Anales de Psicología / Annals of Psychology, 2020)
Many previous studies have discussed the influence of extrinsic factors (e.g. living environment) on academic achievement of children from western China. The present study focused on four non-cognitive factors, self-educational aspiration, self-efficacy, instrumental motivation, and anxiety, which could affect mathematics achievement. The purpose of this study was to investigate the mechanisms how these four non-cognitive factors affected mathematics achievement. 5774 primary school students from 4th and 5th grade in western China participated in this study. A moderated chained mediation model was constructed. The results showed that self-educational aspiration could positively predict mathematics achievement. However, instrumental motivation and anxiety formed chained mediation between self-educational aspiration and mathematics achievement, and negatively predicted mathematics achievement. Besides, self-efficacy played a moderated role in the relationship between self-educational aspiration and anxiety.